Gender and Age/Aging in Popular Culture Representations in Film, Music, Literature, and Social Media - Haring, Nicole; Maierhofer, Roberta; Ratzenböck, Barbara (Aging Studies, 2023)
As social spaces are culturally diverse and digitally networked, the reality of our lives is shaped by processes of globalization and digitization. This leads to the question of whether popular cultures enable or impede (inter-)cultural exchange and global communication. To explore this, the contributors to this volume analyze representations of the intersections of gender and age/ing in cultural and media consumption, such as literature, film, music, and social media. The interconnectedness between gender and aging has been evident since the 1990s and enabled the recognition of age as a cultural category - now is the time to take this intersectional analysis further.